2020
DOI: 10.4037/ccn2020438
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Catheter-Associated Urinary Tract Infections in the Pediatric Intensive Care Unit

Abstract: Background Catheter-associated urinary tract infections are common health care–associated infections and have been associated with increased mortality, morbidity, length of stay, and cost. Prevention strategies are grouped into bundles focused on reducing unnecessary catheter use and promptly removing urinary catheters. Before intervention in the study institution, no urinary catheters were unnecessarily used and compliance with the catheter-associated urinary tract infection bundle was 84%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The majority of the Yemeni HCWs (> 85%) followed good practices in terms of keeping the tubing and collecting bag free from kinking and below the level of the patient’ bladder. Studies reported that these items were complied with at all times, which is congruent with our study [ 14 , 33 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…The majority of the Yemeni HCWs (> 85%) followed good practices in terms of keeping the tubing and collecting bag free from kinking and below the level of the patient’ bladder. Studies reported that these items were complied with at all times, which is congruent with our study [ 14 , 33 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Microscopic analysis of the bacterial biofilms revealed a honeycomb structure, which was difficult for antibiotics to infiltrate, and could result in multidrug resistance through repeated antibiotic use ( 19 ). The use of an indwelling drainage tube, which could reduce the risk for UTI, could be explained by the following: the underlying effect of an indwelling drainage tube was balanced by other characteristics; the bundle compliance to eliminate the dependent loop in the drainage tube through targeted rounds ensured that the appropriate use of the catheter could reduce the risk for UTI ( 20 ); the appropriate indication for the insertion of the drainage tube, standardization of care for the indwelling drainage tube, appropriate management of leaking urinary catheters, urinary catheter days and removal were combined in daily rounds, and the prolonged use of an indwelling drainage tube should be carefully monitored to improve the progression of UTI ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…We did find evidence that APP staffing was associated with decreased risk of experiencing a hospital acquired infections. A possible mechanism for this finding is that APPs were able to spend time implementing evidence-based practices known to reduce these infections, such as line insertion and maintenance bundles, line rounding and daily rounding quality improvement checklists 31–33. In addition, in nursing literature, improvements in staffing have been associated with lower rates of hospital acquired infections 34.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism for this finding is that APPs were able to spend time implementing evidence-based practices known to reduce these infections, such as line insertion and maintenance bundles, line rounding and daily rounding quality improvement checklists. [31][32][33] In addition, in nursing literature, improvements in staffing have been associated with lower rates of hospital acquired infections. 34 When APPs are used in units with physician shortages, they improve unit staffing in ways that may contribute to overall improvements in patient safety outcomes.…”
Section: Discussionmentioning
confidence: 99%